Duty drawback on exports. - Satagopan, P. B.; International Trade Centre UNCTAD/GATT. (Geneva : International Trade Centre UNCTAD/GATT, 1979)
Handbook on duty drawback as a form of export incentive - deals with schemes of duty drawback on exports, manufacture in bond for export and temporary exemption from duty; discusses the scope of drawback, methods of determining drawback rates and procedural simplifications for payment of drawback
osc 25/07/2018
Loans
Keywords: Drawbacks; Tariff